2022
DOI: 10.5194/essd-14-1109-2022
|View full text |Cite
|
Sign up to set email alerts
|

The Reading Palaeofire Database: an expanded global resource to document changes in fire regimes from sedimentary charcoal records

Abstract: Abstract. Sedimentary charcoal records are widely used to reconstruct regional changes in fire regimes through time in the geological past. Existing global compilations are not geographically comprehensive and do not provide consistent metadata for all sites. Furthermore, the age models provided for these records are not harmonised and many are based on older calibrations of the radiocarbon ages. These issues limit the use of existing compilations for research into past fire regimes. Here, we present an expand… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 58 publications
1
15
0
1
Order By: Relevance
“…The climate effect was larger than the CO2 effect across all models for FS, with increases in wind, DD and DTR driving the change. BA Our model results reproduce the global reduction of biomass burning at the LGM observed from ice cores and sedimentary charcoal records (Daniau et al, 2012;Harrison et al, 2022;Power et al, 2008;Rubino et al, 2016). Some studies have indicated the occurrence of high-intensity wildfires on the Palaeo-Agulhas Plain of South Africa, tropical regions, northern Australia, and central China at the LGM (Kraaij et al, 2020;Power et al, 2008;Rowe et al, 2021;Ruan et al, 2020;M.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The climate effect was larger than the CO2 effect across all models for FS, with increases in wind, DD and DTR driving the change. BA Our model results reproduce the global reduction of biomass burning at the LGM observed from ice cores and sedimentary charcoal records (Daniau et al, 2012;Harrison et al, 2022;Power et al, 2008;Rubino et al, 2016). Some studies have indicated the occurrence of high-intensity wildfires on the Palaeo-Agulhas Plain of South Africa, tropical regions, northern Australia, and central China at the LGM (Kraaij et al, 2020;Power et al, 2008;Rowe et al, 2021;Ruan et al, 2020;M.…”
Section: Discussionsupporting
confidence: 73%
“…Changes in GPP and grass cover were responsible for the largest reductions in burning, with these vegetation effects concentrated across Africa and much of Eurasia (see Figure 5). In Amazonia, changes in DD were the most important factor, reducing Comparing the spatial patterns of the simulated BA anomalies with charcoal-based reconstructions of the sign of changes in biomass burning (RPD; Harrison et al, 2022) showed that the best overall match occurred when both the climate and CO2 effect were considered, with a success rate of ~ 39-45% depending on the climate scenario. A successful identification means that the sign of the experiment anomaly and the sign of the RPD charcoalbased reconstructions are the same.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations